Case Report: Microsurgical clipping of a multilobular fenestrated anterior communicating artery aneurysm: technical challenges with video analysis - Erginoglu, Ufuk; Uyaniker, Zeynep Arzum; Ataoglu, Cagdas; Sulaimanov, Umid; Kendirlioglu, Bekir Can; Ak, Huseyin Erdem; Ross, Miner; Baskaya, Mustafa Kemal (Frontiers in Surgery, 2025)
BackgroundThe anterior communicating artery (AComA) is a common site for intracranial aneurysms due to its complex vascular architecture. Fenestrations in the AComA, observed in 7.5%–40% of cases, can disrupt normal blood flow, which increases turbulence and shear stress and heightens the risk of aneurysm formation.Case descriptionWe report the case of a 67-year-old female who presented with headaches. Imaging revealing a 10 mm unruptured multilobular aneurysm arising from the AComA. Microsurgical clipping was performed via a right pterional craniotomy. The fenestrated nature of the AComA only became apparent after intraoperative full dissection of the AComA complex. Intraoperative Doppler ultrasound and indocyanine green angiography were used to evaluate the vascular anatomy, which was followed by the successful clipping of the aneurysm. Postoperative angiography verified complete obliteration, and the patient recovered without neurological deficit.ConclusionThe complexity of the AComA anatomy in this case prompted reflection on the limitations of preoperative imaging and the need for careful intraoperative planning. Although advanced imaging modalities, particularly three-dimensional rotational angiography, are crucial for detecting vascular anomalies, ultra-thin bridging vessels may remain undetected, as occurred in this case. Intraoperative recognition of these structures required real-time adaptation to ensure safe dissection and successful aneurysm clipping To our knowledge, this is the first operative video documenting microsurgical clipping of an unruptured aneurysm within a fenestrated AComA. This case underscores the importance of anticipating anatomical variations and adapting surgical strategies to optimize outcomes in complex cerebrovascular procedures.